2020
DOI: 10.3389/fcell.2020.00088
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Epithelial Cell Proliferation in Peripheral Airways in Bronchiectasis

Abstract: Dilation of bronchi and bronchioles caused by destruction and excessive epithelial remodeling is a characteristic feature of bronchiectasis. It is not known how epithelial progenitor cells contribute to these pathologic conditions in peripheral airways (bronchioles) in bronchiectasis. We aimed to explore the expression levels of signature airway progenitor cells in the dilated bronchioles in patients with bronchiectasis. We obtained the surgically resected peripheral lung tissues from 43 patients with bronchie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Histopathological analysis revealed areas of denuded ciliated epithelium, as well as goblet cell hyperplasia, as common features of the asthmatic airway [10,62]. In addition, bronchiectasis biopsies showed extensive epithelial hyperplasia, with reduced lung progenitor cells, and an enhanced number of self-renewing cells capable of differentiation into ciliated and secretory cells [63]. Such observations may suggest that aberrant epithelial repair mechanisms contribute to the pathophysiology of asthma with associated bronchiectasis.…”
Section: A Fumigatus-induced Epithelial Cell Damagementioning
confidence: 88%
“…Histopathological analysis revealed areas of denuded ciliated epithelium, as well as goblet cell hyperplasia, as common features of the asthmatic airway [10,62]. In addition, bronchiectasis biopsies showed extensive epithelial hyperplasia, with reduced lung progenitor cells, and an enhanced number of self-renewing cells capable of differentiation into ciliated and secretory cells [63]. Such observations may suggest that aberrant epithelial repair mechanisms contribute to the pathophysiology of asthma with associated bronchiectasis.…”
Section: A Fumigatus-induced Epithelial Cell Damagementioning
confidence: 88%
“…The abnormal airway epithelium contributes to both CF and bronchiectasis ( Peng et al, 2020 ; Chen et al, 2018 ; Barbry et al, 2020 ). Insufficient growth and differentiation of epithelial cells can lead to persistent mucosal injury that promotes bacterial colonization and neutrophilic inflammation.…”
Section: Lncrna–mirna Interaction In Chronic Inflammatory Airway Dise...mentioning
confidence: 99%
“…Rao et al found that abnormal ABSCs in COPD resulted in pathologic characteristics including airway fibrosis, inflammation, and mucus hypersecretion [ 7 ]. Peng et al reported that airway progenitor cells were abnormally proliferative in bronchiectasis [ 8 ]. Moreover, growing evidence indicates that the dysfunction of ABSCs plays a crucial role in driving the progression of idiopathic pulmonary fibrosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%